The Effect of Emotional Intelligence and Learning Environment on College Stress of Accounting Students with Self Efficacy as an Intervening Variable at Muhammadiyah University of Sidoarjo: Pengaruh Kecerdasan Emosional, Dan Lingkungan Belajar Terhadap Stres Kuliah Mahasiswa Akuntansi Dengan Self Efficacy Sebagai Variabel Intervening Di Universitas Muhammadiyah Sidoarjo - Eka Putri Sayekti; Sigit Hermawan (Academia Open, 2021)
This study has a background problem of the number of students who are stressed from college to the point of committing suicide and failing to graduate from college. The purpose of this study was to determine the effect of emotional intelligence, and the learning environment on student lecture stress in accounting with self efficacy as an intervening variable at the University of Muhammadiyah Sidoarjo, either directly or indirectly. The sample used in this study were accounting students at the Muhammadiyah University of Sidoarjo. The analytical tool used is the Partial Least Square analysis with validity and reliability tests of both the outer model and the inner model using the Smart PLS program. Primary data is obtained from questionnaires whose measurements use a Likert scale. The results showed that emotional intelligence has an effect on the self-efficacy of accounting students at the Muhammadiyah University of Sidoarjo. The learning environment affects the self-efficacy of accounting students at the Muhammadiyah University Sidoarjo. Emotional intelligence affects college stress in accounting students at Muhammadiyah University Sidoarjo. The learning environment has an effect on college stress in accounting students at the Muhammadiyah University of Sidoarjo. Self-efficacy has an effect on college stress in accounting students at Muhammadiyah University Sidoarjo. Emotional intelligence affects college stress mediated by self-efficacy of accounting students at Muhammadiyah University Sidoarjo. Learning environment affects college stress mediated by self-efficacy of accounting students at Muhammadiyah University Sidoarjo